Accelerated Storage Testing of Vacuum-Dried Lactobacillus acidophilus TISTR 1338 for Feed - Apichet Muenaram; Bhundit Innawong; Imrana Niaz Sultan; Muhammad Waseem Khan; Hamza Ghilzai; Afrasiab Khan Tareen; Pramuk Parakulsuksatid (Microbiology Research)
Lactic acid bacteria (LAB) are widely used to produce various food products, adding flavor, texture, and health benefits. The bacteria are commonly grown on expensive nutrients like glucose, sucrose, and yeast extracts, which makes them commercially unappealing. In the current study, Lactobacillus acidophilus TISTR 1338 culture was studied using spent cell yeast as a nitrogen source and molasses as a carbon source. The drying process used to create starter cultures of Lactobacillus acidophilus TISTR 1338 was vacuum drying. After vacuum drying, this bacterium had a survival rate of 8.08 log CFU/g. The dried strain survived for four months at 37 °C. With wasted cells at 0.5%, molasses concentration at 11% at 2.14 109 CFU/mL at 22 h, precise growth rate at 0.39 h−1, and yield cell mass at 1.67 1011 CFU/g sugar, yeast produced the maximum cell mass. The lower viability of the tested strain was induced by a higher temperature during this prolonged storage. Meanwhile, dehydrated starter culture was subjected to accelerated storage testing at 50, 60, and 70 °C. To determine the vacuum-dried Lactobacillus acidophilus TISTR 1338′s long-term storage viability, a temperature-dependent prophecy model was created. Molasses and spent cell yeast serve as promising carbon and nitrogen sources when optimized conditions are employed. The study also suggests that vacuum drying is a promising method for producing dried cells suitable for non-refrigerated storage conditions.